LANDUSE CHANGES AND VEGETATION HEALTH ASSESSMENT OF NGEL NYAKI FOREST RESERVE, TARABA STATE, NIGERIA - Akomolafe, Gbenga Festus; Anumeh, Albert (FUDMA Journal of Sciences, 2025)
The preservation of forest ecosystems is of paramount importance in the face of global environmental challenges. In Nigeria, the Ngel Nyaki forest reserve (NNFR) represents a critical area of biodiversity and plays a significant role in climate regulation and water resource management. This study comprehensively assessed the extent of landuse and vegetation changes in the forest reserve over the past 30 years by utilising Remote Sensing (RS) technology and Geographic Information System (GIS) analysis. Landsat 4-5 and Landsat 8 images were obtained to classify the landuse and land cover for both the catchment area and the forest using the maximum likelihood algorithm. The vegetation health indicated by the Normalised Difference Vegetation Index (NDVI), Enhanced Vegetation Index (EVI) and Green Chlorophyll Index (GCI) from 1993 to 2023 were determined. The results revealed that there was a decrease of 10,626.03 hectares (6.24%) in the dense forest and the open land increased to 22,067.73 hectares (4.49%) of the total land area of the catchment area from 1993 to 2023. Same trend was observed in the NNFR whereby the dense forest decreased to 126.54 hectares (80.01%). From 1993 to 2023, the mean NDVI and GCI slightly decreased to 0.28 and 1.86 respectively while NDWI and EVI maintained their statuses. SLAVI increased from 0.73 in 1993 to 0.84 in 2023. These findings underscore the pressing need for effective conservation measures to mitigate the adverse impacts of deforestation on biodiversity and ecosystem services of this forest reserve.
Keywords: Deforestation; Degradation; NDVI; Reserved forest; Vegetation indices